Robotic limited local resection of duodenal juxta‐ampullary neoplasms. Issue 2 (23rd November 2020) - Cho, Hye Jung; Jang, Jae Young; Jeong, Sung Yub; Kang, In Cheon; Lee, Sung Hwan; Choi, Sung Hoon
ABSTRACT: Background: The unique and complex anatomical location of duodenal juxta‐ampullary neoplasms complicates selection of the appropriate surgical strategy. For benign or borderline tumours, surgical local resection can be an appropriate treatment option, and robotic surgical systems can help perform minimally invasive local resection of these lesions. Methods: Between December 2014 and December 2019, 10 patients who underwent robotic local resections for duodenal juxta‐ampullary tumours were reviewed. Results: All patients successfully underwent robotic local resection of the duodenum, preserving the ampulla of Vater without conversion. The mean tumour size was 2.2 cm. Final pathology consisted of gastrointestinal stromal tumour, neuroendocrine tumour, low grade and high grade dysplasia, ectopic pancreas, and well‐differentiated adenocarcinoma (T1a). There were no postoperative complications or recurrences. Conclusion: With accurate preoperative diagnosis and careful selection of patients, local resection of the duodenum for juxta‐ampullary benign or borderline tumours using robotic surgical system is an attractive treatment option.